Evaluating pimavanserin as a treatment for psychiatric disorders: A pharmacological property in search of an indication. (2nd September 2021) - Davis, John; Zamora, Daisy; Horowitz, Mark; Leucht, Stefan
ABSTRACT: Introduction : Pimavanserin is FDA-approved to treat hallucinations and delusions associated with Parkinson's disease psychosis. As a potent 5-HT2A inverse agonist/antagonist, it could be efficacious in other psychiatric disorders. Recently, several studies have investigated this potential. Areas covered : The authors review the efficacy and adverse effects of pimavanserin for hallucinations in dementia, major depression, and schizophrenia. Expert opinion : Two controlled studies suggest pimavanserin has potential as a treatment for hallucinations in dementia. In patients with depression who did not respond to antidepressant treatment, pimavanserin augmentation was efficacious in a phase 2 study. Pimavanserin augmentation also alleviated sexual side effects of SSRI and SSNI. However, Acadia Pharmaceuticals stated in a press release that it does not plan further antidepressant trials based on its phase 3 trial, which showed a nonsignificant trend toward an antidepressant effect. Since almost all existing antipsychotics fail to substantially benefit negative symptoms, better treatments are needed. Pimavanserin augmentation of antipsychotics did benefit negative symptoms (effect size≈0.2) but failed to reduce the total PANSS score significantly in two large, well-controlled double-blind studies. Pimavanserin has a good safety profile.